Organic carbon monoxide prodrug, BW-CO-111, in protection against chemically-induced gastric mucosal damage - Dominik Bakalarz; Marcin Surmiak; Xiaoxiao Yang; Dagmara Wójcik; Edyta Korbut; Zbigniew Śliwowski; Grzegorz Ginter; Grzegorz Buszewicz; Tomasz Brzozowski; Jakub Cieszkowski; Urszula Głowacka; Katarzyna Magierowska; et al. (Elsevier, 2021)
Metal-based carbon monoxide (CO)-releasing molecules have been shown to exert anti-inflammatory and anti-oxidative properties maintaining gastric mucosal integrity. We are interested in further development of metal-free CO-based therapeutics for oral administration. Thus, we examine the protective effect of representative CO prodrug, BW-CO-111, in rat models of gastric damage induced by necrotic ethanol or aspirin, a representative non-steroidal anti-inflammatory drug. Treatment effectiveness was assessed by measuring the microscopic/macroscopic gastric damage area and gastric blood flow by laser flowmetry. Gastric mucosal mRNA and/or protein expressions of HMOX1, HMOX2, nuclear factor erythroid 2-related factor 2, COX1, COX2, iNos, Anxa1 and serum contents of TGFB1, TGFB2, IL1B, IL2, IL4, IL5, IL6, IL10, IL12, tumor necrosis factor α, interferon γ, and GM-CSF were determined. CO content in gastric mucosa was assessed by gas chromatography. Pretreatment with BW-CO-111 (0.1 mg/kg, i.g.) increased gastric mucosal content of CO and reduced gastric lesions area in both models followed by increased GBF. These protective effects of the CO prodrug were supported by changes in expressions of molecular biomarkers. However, because the pathomechanisms of gastric damage differ between topical administration of ethanol and aspirin, the possible protective and anti-inflammatory mechanisms of BW-CO-111 may be somewhat different in these models.